Mapping dan Monitoring Kuat Sinyal Sel Menggunakan Handphone CDMA Berbasis Android - Roselina Febriati (Politeknik Negeri Malang, 2015)
In this study, an application was made that functions to map and monitor the signal strength of CDMA network cells using Android-based CDMA cellphones. This application functions to determine the signal quality of a CDMA network when the mapping and monitoring process is carried out. Cell signal strength information in Mappingke in a map based on google map. Meanwhile, information from monitoring results can be saved on the SD Card of the handphone with the .csv file format. the results of testing the information that can be map to the google map are the position of the BTS, the position of the MS, the value of RSSI and Ec / Io. Meanwhile, the monitoring result information that can be stored in a mobile SDCard is time, network type, CDMA cell identity which includes SID, NID, BID, base station latitude and longitude base station, MS position, cell signal strength which includes RSSI, Ec / Iodan SNR, along with the distance between MS and BTS.The CDMA cell identity information displayed by the application on the Samsung Galaxy Young mobile phone in the Malang area is correct and in accordance with the operator's data. The mapping information of RSSI and Ec / Io values ??into the google map is correct according to the value of the RSSI and Ec / Io base stations captured by the mobile station.